Beyond the Support Function: How Human Resource Development Becomes a Strategic Driver of the Competitiveness of SMEs: A Bibliometric Analysis - Anggi Pasca Arnu; Disman; Rofi Rofaidah; Syamsul Hadi Senen; Tjutju Yuniarsih (Global Research Collaboration, 2026)
Human Resource Development (HRD) has attracted increasing academic attention as a strategic lever for enhancing the performance and sustainability of Small and Medium-Sized Enterprises (SMEs). Despite a growing body of literature, no comprehensive bibliometric map of the field exists, leaving its intellectual structure and thematic evolution largely uncharted. This study systematically analyses research trends, thematic evolution, influential studies, and global collaboration patterns in HRD in SMEs using a bibliometric approach. A total of 859 documents were retrieved from the Scopus database through a systematic identification, deduplication (n = 0 duplicates removed), screening, and eligibility process. Publication and citation trends were analysed using Microsoft Excel, and keyword co-occurrence networks and overlay visualisations were produced using VOSviewer (minimum co-occurrence threshold: ≥3). Results reveal a significant increase in HRD in SMEs publications particularly after 2015. Highly cited studies emphasise digital transformation, performance measurement systems, sustainability, and capability development. Research is globally distributed, with dominant contributions from developed countries and increasing participation from emerging economies. Network and overlay visualisations confirm the field is increasingly multidisciplinary, integrating human capital, digital transformation, sustainability, and Industry 4.0, with emerging themes including green HRM, resilience, and co-creation. This study provides a large-scale bibliometric mapping of the HRD in SMEs research field, confirming that HRD has evolved from a peripheral support function into a strategic research domain that bridges human capital theory, digital transformation, and sustainability.